2014
DOI: 10.1039/c4dt00074a
|View full text |Cite
|
Sign up to set email alerts
|

4,2′:6′,4′′-Terpyridines: diverging and diverse building blocks in coordination polymers and metallomacrocycles

Abstract: 4,2':6',4''-Terpyridine (4,2':6',4''-tpy) is one of the less well documented isomers of the well-established bis-chelating 2,2':6',2''-terpyridine. The N-donors of the outer rings in 4,2':6',4''-tpy subtend an angle of 120°, leading to a description of 4,2':6',4''-tpy as a divergent ligand. Because it typically binds metal ions through the outer N-donors only, 4,2':6',4''-tpy is an ideal linker for combination with metal nodes (often geometrically flexible d(10) ions) in coordination polymers and metallomacroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
127
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 44 publications
5
127
0
Order By: Relevance
“…[22,31] During the course of our investigations of the coordination chemistry of the ferrocenyl-functionalized 4,2':6',4''-and 3,2':6',3''-terpyridines shown in Scheme 2, Tian and coworkers reported that 2 reacts with ZnCl2 and ZnBr2 to give the discrete metallohexacycles 9…”
Section: Coordination Polymer Versus Metallomacrocycle Assembly With mentioning
confidence: 99%
See 1 more Smart Citation
“…[22,31] During the course of our investigations of the coordination chemistry of the ferrocenyl-functionalized 4,2':6',4''-and 3,2':6',3''-terpyridines shown in Scheme 2, Tian and coworkers reported that 2 reacts with ZnCl2 and ZnBr2 to give the discrete metallohexacycles 9…”
Section: Coordination Polymer Versus Metallomacrocycle Assembly With mentioning
confidence: 99%
“…[21] Ligand 2 reacts with ZnCl2 and ZnBr2 to give discrete metallohexacycles similar to those obtained with other 4'-substituted 4,2':6',4'-tpy ligands. [22] 1D-coordination polymers result when 2 is treated with ZnI2, Zn(NCS)2 and Zn(OAc)2. We now report the synthesis and coordination behaviour of 1-(3,2':6',3''-terpyridin-4'-yl)ferrocene (3, Scheme 2) with ZnCl2 and ZnBr2, and also demonstrate competitive assembly pathways to different structure types using ligands 2 and 3.…”
Section: Introductionmentioning
confidence: 99%
“…Different polymeric architectures (dendrimers, hyperbranched, and linear) containing or based on terpyridine have been published [1][2][3]. Whereas there are a large number of publications concerned with polymers bearing different terpyridine ligands, the preparation of the first, terpyridine-modified, cellulose polymer was reported during 2012 in Professor Newkome' laboratories at the University of Akron through his collaboration with our group at the National Research Centre in Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…The use of 4,2':6',4''-terpyridine (4,2':6',4''-tpy) ligands as metal-binding domains for the assembly of coordination polymers is highly attractive and topical [1]. Of the three nitrogen donors in 4,2':6',4''-tpy, only the outer two typically bind metal ions leading to a divergent, V-shaped building block with well-defined directionality.…”
Section: Introductionmentioning
confidence: 99%